Sex differences in comorbidities and COVID-19 mortality–Report from the real-world data - Yilin Yoshida; Jia Wang; Yuanhao Zu (Frontiers in Public Health, 2022)
BackgroundThe differential effect of comorbidities on COVID-19 severe outcomes by sex has not been fully evaluated.ObjectiveTo examine the association of major comorbidities and COVID-19 mortality in men and women separately.MethodsWe performed a retrospective cohort analysis using a large electronic health record (EHR) database in the U.S. We included adult patients with a clinical diagnosis of COVID-19 who also had necessary information on demographics and comorbidities from January 1, 2016 to October 31, 2021. We defined comorbidities by the Charlson Comorbidity Index (CCI) using ICD-10 codes at or before the COVID-19 diagnosis. We conducted logistic regressions to compare the risk of death associated with comorbidities stratifying by sex.ResultsA total of 121,342 patients were included in the final analysis. We found significant sex differences in the association between comorbidities and COVID-19 death. Specifically, moderate/severe liver disease, dementia, metastatic solid tumor, and heart failure and the increased number of comorbidities appeared to confer a greater magnitude of mortality risk in women compared to men.ConclusionsOur study suggests sex differences in the effect of comorbidities on COVID-19 mortality and highlights the importance of implementing sex-specific preventive or treatment approaches in patients with COVID-19.